Impact of age- and gender-specific cut-off values for the fecal immunochemical test for hemoglobin in colorectal cancer screening. Issue 5 (May 2016) - ,; Lanas, Angel; Gonzalez-Rubio, Francisca; Moya-Calvo, Alberto; Polo-Tomas, Mónica; Pilar Roncales, Maria; Sebastian-Martínez, Pilar; Valencia-Doblas, María Ángeles; Valero-Capilla, Nieves; Bujanda, Luis; Alkiza, María E.; Altzibar, Jone; et al.
Abstract: Background: There is no information on the impact of age and gender on the diagnostic yield of different positivity thresholds for the fecal immunochemical test for hemoglobin (FIT). Objectives: To evaluate the performance of this test at distinct positivity cut-offs in a population-based colorectal cancer (CRC) screening program. Methods: CRC detection rate (DR), and analysis of resources were evaluated retrospectively, at different cut-offs of FIT (20, 25, 30, 35 and 40 μg Hb/g) respect to a reference value (15 μg Hb/g), according to age and gender, in a screening population of 10, 611 participants of the ColonPrev study (Quintero. NEJM 2013). Results: At the reference cut-off value, 36 CRC and 252 advanced adenomas (AA) were diagnosed. Increasing the cut-off in women ≤60 years decreases colonoscopies performed by 44.5% without modifying the CRC (DR). Same CRC DR was observed in men ≤60 years and women >60 years increasing cut-off at 25–30 μg Hb/g. In men >60 years, all increases in the cut-off affected the CRC DR, especially when the cut-off was increased from 35 to 40 μg Hb/g (CRC miss rate 25%). Conclusions: To improve the performance of FIT in CRC screening programs, FIT cut-offs could be individualized by age and gender.